Bilateral SCC of the Parotid Gland: A Case Report and Literature Review - Majdinasab, Niloofar (Journal of Otorhinolaryngology and Facial Plastic Surgery, 2020)
Background: Salivary gland neoplasms represent rare cancers. Bilateral tumors of the parotid gland is very rare. Case Presentation: An old man with bilateral parotid mass starting from 3 months ago, he had a history of SCC of scalp. Conclusions: The above case of metachronous bilateral squamous carcinoma is exceedingly uncommon. Treatment of malignant bilateral parotid tumors requires bilateral total parotidectomy with lymph node sampling